Framing Analysis of Media Coverage on Plastic Waste Reduction in Medan City on Kompas.com - Triwulan, Dewi; Sikumbang, Ahmad Tamrin (Journal Analytica Islamica, 2025)
This study aims to analyze how media framing by Kompas.com in reporting plastic waste reduction in Medan City and its impact on public perception. Using a qualitative approach through content analysis and Pan and Kosicki's framing theory, this study identifies the syntactic, script, thematic, and rhetorical structures of the news studied. The results show that Kompas.com emphasizes more on regulatory and technical aspects, but does not touch on the emotional and personal aspects of society. A survey of 21 respondents showed that the majority were neutral towards the influence of news reporting, indicating that the effectiveness of framing in shaping public awareness and participation is not yet optimal. This study concludes that a more humanistic, contextual, and local narrative-based media approach is needed to increase public involvement in environmental issues.